MENINGKATKAN HASIL BELAJAR LOMPAT TINGGI MELALUI PERMAINAN POS BERANGKAI PADA SISWA KELAS IV SDN SIDALANG 02 KECAMATAN TERSONO KABUPATEN BATANG TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to improving learning outcomes through the game's high jump at the post berangakai Sidalang fourth grade students of SDN 02 Batang District Tersono In 2012 / 2013. This research is a class action. Actions performed each cycle includes: (1) planning (2) implementation (3) observation, and (4) reflection. Research subjects Elementary School fourth grade students of the school year Sisalang 02 2012/2013 as many as 12 students. Techniques of data collection by observation and research tests the ability of the high jump learning outcomes. Using descriptive data analysis techniques to determine the percentage of complete learn classical student outcomes. The results of the first cycle showed that 58.33% or 7 students achieve mastery learning, so continued kesiklus II and the results showed that an increase in the percentage of completion of learning outcomes in the category of 83.3% or 10 students achieve mastery learning of 12 students. Because classical completeness percentage of student learning outcomes has reached 83.3%, the researchers of this class action have reached an indicator of success. Conclusions This study is the high jump learning through games can increase the ability of post sequential learning outcomes Sidalang fourth grade students of SDN 02 Batang District Tersono Academic Year 2012/2013.